Implementasi Manajemen Pendidikan Islam dalam Penguatan Kinerja Guru: Studi Kasus di Madrasah Tsanawiyah Berbasis Pesantren - Yulis Setiani; Widya Andriyani (IQRO: Journal of Islamic Education, 2025)
This study examines the implementation of Islamic educational management in strengthening teacher performance in a pesantren-based madrasah. The study is motivated by the gap between ideal management practices and the limited structural conditions faced by teachers, including workload, welfare, and resource constraints, which affect teaching performance. This research aims to analyze how management functions are implemented and how they contribute to strengthening teacher performance. A qualitative case study approach was employed, with data collected through participatory observation, in-depth interviews with 12 informants, and document analysis. The findings reveal that management practices are carried out adaptively rather than structurally optimal, where leadership, religious values, and organizational culture play a crucial role in reinforcing teacher performance. Although limitations such as low welfare and dual professions persist, teachers maintain their professional commitment through value-based motivation. The study highlights an adaptive management model as a contextual approach in improving teacher performance in resource-limited Islamic educational institutions.